Monitoring and Evaluating Education Systems: Insights from European Countries - Shakirova Araily Dalelovna; Che Xiaodan; Adilgazy Akku (Scientific Research and Experimental Development, 2025)
Education systems require continuous monitoring and evaluation to ensure quality and effectiveness. This paper explores the mechanisms European countries use to assess educational outcomes, maintain high standards, and enhance learning environments. It examines standardized assessments, institutional evaluations, and teacher performance reviews while comparing these approaches to international standards. Furthermore, the paper discusses how European countries manage examinations and monitor the educational process, providing insights into best practices and future directions. Additionally, the study highlights the principles, criteria, and rules of the European Security System Model for maintaining education quality, emphasizing equity, accountability, and data-driven decision-making